Current Practices and Preferences of Fellows and Program Directors on Taking the Certifying Examination During Subspecialty Fellowships. Issue 8 (August 2021) - Gupta, Ankita; Meriwether, Kate; Martin, Alexandra; Pierson, Rebecca C.
Abstract : Objective: Fellows in obstetrics and gynecology subspecialties often take their oral specialty certifying examination (referred to here as generalist certifying examination [GCE]) during fellowship. We sought to compare the opinions of current fellows and program directors (PDs) regarding their program's handling of GCE during fellowship. Methods: In this online, survey-based study, fellows and PDs currently affiliated with an accredited fellowship in maternal-fetal medicine, reproductive endocrinology and infertility, female pelvic medicine and reconstructive surgery, or gynecologic oncology (GO) received the link to an unvalidated survey. This survey was open for 8 weeks, between April and June 2020; eligible participants were contacted through their programs, society Listserv, and social media and received 3 reminder e-mails. Results: Final analysis included 408 (408/834; response rate, 49%) fellows and 163 (163/223; response rate, 73%) PDs across the 4 subspecialties. There were significant differences in whether fellows responded that they were required or encouraged to take the GCE (52% maternal-fetal medicine, 65% reproductive endocrinology and infertility, 39% female pelvic medicine and reconstructive surgery, 8% GO; P < 0.01) during fellowship. Fewer GO fellows noted that they were permitted to use educational funds for GCE when compared with the other subspecialties ( P < 0.01). Most fellows responded that the inability to take GCE during fellowship would decrease their satisfaction with fellowship, and this was significantly higher than PD estimates (78% vs 39%, P < 0.01). Conclusions: There are significant differences in reported ability to take GCE during fellowship across different obstetrics and gynecology subspecialty fellowships. Program directors significantly underestimate fellow dissatisfaction with inability to take GCE during fellowship. Abstract : Supplemental digital content is available in the text.